2022
DOI: 10.2166/aqua.2022.017
|View full text |Cite
|
Sign up to set email alerts
|

Combined enhancement of evaporation and condensation rates in the solar still for augmenting the freshwater productivity using energy storage and natural fibres

Abstract: The freshwater production in a conventional solar still (CSS) is very less and it can be enhanced by either enhancing evaporation or condensation rates or both in the solar still. Therefore, the current investigation focused on enhancing both the evaporation rate in the absorber basin and the condensation rate over the top glass simultaneously. In this regard, the evaporation rate is enhanced by using a hollow-finned absorber basin with energy storage and novel pond fibres in the absorber basin. Likewise, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Solar still performance was analyzed both experimentally and theoretically [3]. The experimental and theoretical values were completely consistent with one another [4]. The research also showed that solar intensity and the temperature of the incoming water had a direct bearing on the effectiveness of instantaneous stills.…”
Section: Introductionmentioning
confidence: 53%
“…Solar still performance was analyzed both experimentally and theoretically [3]. The experimental and theoretical values were completely consistent with one another [4]. The research also showed that solar intensity and the temperature of the incoming water had a direct bearing on the effectiveness of instantaneous stills.…”
Section: Introductionmentioning
confidence: 53%
“…The water and absorber temperatures of solar still with PCM are significantly improved by about 10% using RT-58 under the absorber basin. 7 Solar still with ball marbles 36.67 1.9 5.7 Suraparaju and Natarajan 30 Solar still with PCM and natural fibres 126.90 1.6 3.6 Suraparaju and Natarajan 37 Solar still with hollow fins & PCM 41.67 2.3 6.3 Sampathkumar et al 49 Solar still with composite PCM 64% 2.28 6.2 Modi et al 50 Solar still with nanofluids 58.25 1.5 6.9 Nayi and Modi 51 Pyramid solar still with energy storage 11.35 2.6 11.3…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to its high thermal conductivity, an internal heat absorbing surface of 0.04 mm aluminium sheet coated with the selective coating is chosen. 30,31 In addition, suitable precautions are taken to prevent water leaks. The experimental setup is developed using traditional fabrication and painting techniques.…”
Section: Methodsmentioning
confidence: 99%
“…The uncertainties in measuring instruments are estimated using the following relation (Elminshawy et al , 2022; Suraparaju and Natarajan, 2022b): …”
Section: Methodsmentioning
confidence: 99%